Magnetic resonance imaging metal artifact reduction for eye plaque patient with dental braces - Gach, H. Michael (J Contemp Brachytherapy, 2017)
PURPOSE: To determine if metal artifact reduction can minimize magnetic susceptibility artifacts in the orbits for an eye plaque brachytherapy patient with metallic dental braces. MATERIAL AND METHODS: A 62-year-old female patient with a choroidal melanoma in the right eye received a 1.5 T magnetic resonance imaging (MRI) simulation for 3D eye plaque brachytherapy planning. The protocol included conventional 3D T(1)-weighted and 2D T(2)-weighted MRIs. A vendor-supplied T(2)-weighted metal artifact reduction sequence was added to the protocol to reduce magnetic susceptibility artifacts from the metallic dental braces. The metal artifact reduction sequence combined turbo spin echo acquisitions, high RF excitation and readout bandwidths, and view angle tilting and slice encoding for metal artifact correction with z-shimming to correct in-plane and through-plane image distortions, respectively. RESULTS: Dental braces caused significant signal loss and image distortion in the orbits on the conventional T(1)-weighted and T(2)-weighted MRIs, and the MRIs were unusable for treatment planning. The metal artifact reduction sequence with 13 z-phase encodes minimized distortion and signal loss in the orbits, allowing the tumor to be clearly delineated. CONCLUSIONS: T(2)-weighted MRI with metal artifact reduction was successfully applied to minimize artifacts in the orbits resulting from the dental braces, thus allowing the MRIs to be used in 3D brachytherapy treatment planning.